Morphometry and histochemistry of the semitendinosus muscle of tufted capuchin monkeys (Cebus apella Linnaeus, 1758) - Roque, D. D.; Andreo, J. C.; De Oliveira, J. A.; Roque, J. S.; Buchaim, R. L.; Rodrigues, A. C. (Blackwell Verlag Gmbh, 2003)
Considering monkeys are animals closely related to the human, and semitendinosus muscle has been used in many postural research experiments, we have decided to study its histochemical characteristics. Samples were removed from the proximal, middle and distal regions of the semitendinosus muscles of five adult male tufted capuchin monkeys and observed for reaction with m-ATPase (with alkaline and acid pre-incubation), nicotinamide adenine dinucleotide tetrazolium reductase, and haematoxylin and eosin. The muscle fibres were classified as fast glycolytic (FG), fast oxidative glycolytic (FOG) and slow oxidative (SO) and quantified in terms of frequency and area. The three regions of the semitendinosus muscle showed no significant differences in frequency or area of the respective fibre types, and therefore the muscle can be considered histoenzymologically homogeneous. FG fibres presented higher frequencies and larger areas. The sum of FOG and SO fibres was 57.5%, suggesting that the semitendinosus muscle of the tufted capuchin monkey is adapted to an action involved in posture maintenance and in long arboreal dislocation. The present data agrees with the notion of differentiated quadrupedalism in some primates, which support a lower percentage of their weight on the fore limbs.